Mutant p53 – Heat Shock Response Oncogenic Cooperation: A New Mechanism of Cancer Cell Survival - Alexandrova, Evguenia M.; Marchenko, Natalia D. (Frontiers in Endocrinology, 2015)
The main tumor suppressor function of p53 as a ‘guardian of the genome’ is to respond to cellular stress by transcriptional activation of apoptosis, growth arrest or senescence in damaged cells. Not surprisingly, mutations in the p53 gene are the most frequent genetic alteration in human cancers. Importantly, mutant p53 (mutp53) proteins not only lose their wild-type tumor suppressor activity, but also can actively promote tumor development. Two main mechanisms accounting for mutp53 proto-oncogenic activity are inhibition of the wild-type p53 in a dominant-negative fashion and gain of additional oncogenic activities known as gain-of-function (GOF). Here we discuss a novel mechanism of mutp53 GOF, which relies on its oncogenic cooperation with the heat shock machinery. This coordinated adaptive mechanism renders cancer cells more resistant to proteotoxic stress and provides both, a strong survival advantage to cancer cells and a promising means for therapeutic intervention.